La Catalogna in Dante (dal Fiore alla Monarchia). - Pinto, Raffaele (Scripta, 2022)
The article analyses and relates four Dante passages in which Catalonia is named (or evoked): from the Fiore, from the Commedia, from the De Vulgari Eloquentia and from the Monarchia, in which emerges, on the one hand, an organic idea (even if subjective), of the place that Catalonia occupies in the European linguistic and political space, and on the other the coherence of these approaches